Otimização da sensibilidade de detecção de sensores óticos baseados em moléculas fotônicas - Junior, Valnir Carlos da Silva (2021)
The integrated photonics has been consolidated in the last years in part by the ability to meet the recent demand for the miniaturization of photonic devices. Waveguides and optical microcavities stand out among the main components used in integrated photonics. Waveguides consist of structures capable of guiding electromagnetic waves between their starting and endpoints, based on the difference in the refractive indices of two or more materials to keep light confined by guiding them inside the chip. The optical microcavities are simple photonic structures, mostly in the form of disks or rings, which allow the photons to be strongly confined in a tiny volume. Several integrated photonic devices take advantage of the optical characteristics of these structures, which combined, guarantee the design of integrated photonic chips, fabricated in laboratories of universities, companies, and foundries. One of the largest applications of integrated photonic chips is in optical sensors, called lab-on-a-chip, which allows several lab functions on a single chip in order to achieve high-performance automation and screening. In particular, sensors based on photonic molecules (PMs), which are combinations of optical microcavities coupled with each other, use a detection method linked to the variation of resonances of the microcavities in the presence of a change in the refractive index of the environment around the microcavities. The resolution of these sensors is highly dependent on the dimensions of the transverse session of the waveguide where the light is confined. One of the main challenges of this type of sensor is the optimization of its sensitivity, without there being major changes in the fabrication methods to obtain them once they are well established in the industry. In this sense, the focus of this project was to investigate methods to increase the sensitivity of integrated sensors based on PMs from the optimization of the dimensions of the components that constitute them to the implementation of strangulation in the waveguide that forms the detection rings. This strangulation will ensure an increase in the evanescence of the propagating modes in these cavities, responsible for the detection of the sensors, increasing significantly its sensitivities.